Diversity of Dominant Peripheral T Cell Receptor Clone and Soluble Immune Checkpoint Proteins Associated With Clinical Outcomes Following Immune Checkpoint Inhibitor Treatment in Advanced Cancers - Li, Ye; Wang, Jiaqian; Wu, Liangliang; Li, Xiaoting; Zhang, Xiaoyun; Zhang, Guoqing; Xu, Shengqiang; Sun, Shengjie; Jiao, Shunchang (Frontiers in Immunology, 2021)
Dynamic changes of the peripheral T cell receptor (TCR) and soluble receptors and ligands (sRLs) have the potential to be used as biomarkers to monitor the evolution of the immune system in tumor patients undergoing immunotherapy. These functional biomarkers could be used to predict immune response to treatment with immune checkpoint inhibitors (ICIs) and to provide high-value information on the immune function status of cancer patients, thereby helping physicians to make effective clinical decisions. We collected paired pre- and post-treatment peripheral blood samples from 31 solid tumor patients treated with ICIs. TCR and sRL status were investigated using next-generation sequencing and magnetic bead panels. We found that the diversity of the dominant TCR clone at baseline was correlated with durable clinical benefit in patients receiving single-agent treatment. The D50 index, the diversity from the cumulative 50% of the total complementary determinant region 3, was obtained during treatment. A significant difference in progression-free survival was demonstrated between the D50 high and D50 low groups. This result was validated in an independent cohort. A signature including soluble immune checkpoint proteins (sICPs) was identified. Upregulation of the signature during treatment was correlated with durable clinical benefit. All these results indicate that a novel biomarker based on peripheral TCR and sICPs has the potential to be used in prognostic prediction and for rapid determination of therapeutic outcomes in patients treated with immune checkpoint inhibitors.